Screening of Potential Probiotic Vibrio sp. Against Vibriosis in the Litopenaeus vannamei - Munti Sarida; Esti Harpeni (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
Vibriosis is a bacterial disease generated by Vibrio sp., particularly V. harveyi that becomes the biggest cause of up to 100% shrimp mortality. Using antibiotics as the curative step is not applicable anymore, because of the residual effects to the shrimp and environment and the resistant effects to the humans as well. The purpose of this study was to screen potentially probiotic from strain Vibrio sp. that could inhibit V. harveyi as an effort of handling vibriosis diseases. Water sample from the shrimp ponds were isolated and purified in SWC-agar and TCBS-agar and then were incubated overnight at the room temperature. Bacterial concentrations were calculated using MC Pharland method and spectrophotometer. In vivo test was conducted for the best candidate of potential probiotic isolate, i.e. CP1. Challenged test was leaded within 4 different bacterial concentrations as the treatments and 2 replications using 10 shrimps as the tested organisms per aquarium. The treatments were 107 CFU/ml CP1 VS 107 V. harveyi MR5339 RifR (1), 106 CFU/ml CP1 VS 107 V. harveyi MR5339 RifR (2), 105 CFU/ml CP1 VS 107 V. harveyi MR5339 RifR (3) and PBS (4) as the control. Our study showed that the Survival Rate of the tested organisms was 90% in the treatment 1. This result indicated the capability of growth inhibition of the candidate probiotic bacterium against V. harveyi. Presumably, Vibrio sp. could be used in the vanamei culture as the probiotic. Finally, the candidate probiotic bacterium was identified as Vibrio furnissii.